Konstruktionen der Fremde : Erfahren, verschriftlicht und erlesen am Beispiel Japan - Schaffers, Uta (Spectrum Literaturwissenschaft ;, 2006)
The book examines how and under what conditions the?alien? is first experienced in a concrete encounter and is then constructed in writing and reading, i.e. is made available in texts and then re-created in the process of text reception. This process is.